ASEAN di Tengah Rivalitas AS dan Cina: Kerja sama ASEAN dengan RCEP dalam Mengurangi Dampak Perang Dagang - Febrina Damayanti; Noviar Indira Mikayla Putri; Retno Sri Wahyuni; M. Rahadian Prayoga; Giovani Kevin N.W. (Indonesian Perspective, 2018)
Rivalry among the US and Cina about trade war gives enormous effects towards many states around the world, including ASEAN. ASEAN region is the central market on Pacific. Because of this rivalry, every Cina’s export to US will decrease about 10%, and also reduce 1.1% economy growth in ASEAN. This phenomenon emerges the big question concerning the role of ASEAN. This research paper will answer the role of ASEAN as the multilateral organization on balancing their interests in the middle of trade war. Afterwards, this paper focuses on the topics of rivalry between US and Cina related to economics. The discussion is divided into two main points, first is about the trade war, and second is the role of RCEP to establish the balance of ASEAN’s economy. International cooperation on liberal perspective is used to analyze these case problems. This paper argues that ASEAN is trying to impetus cooperation between its member for facing the challenge of the US and Cina’s trade war. Cooperation is the best way for ASEAN seeing this phenomenon.Keywords: US, Cina, trade war, economy, liberalism